The Treatment of Melioidosis - Timothy J.J. Inglis (MDPI AG, 2010)
Melioidosis is a complex bacterial infection, treatment of which combines the urgency of treating rapidly fatal Gram negative septicaemia with the need for eradication of long-term persistent disease in pulmonary, soft tissue, skeletal and other organ systems. Incremental improvements in treatment have been made as a result of multicentre collaboration across the main endemic region of Southeast Asia and northern Australia. There is an emerging consensus on the three main patterns of antimicrobial chemotherapy; initial (Phase 1) treatment, subsequent eradication (Phase 2) therapy and most recently post-exposure (Phase 0) prophylaxis. The combination of agents used, duration of therapy and need for adjunct modalities depends on the type, severity and antimicrobial susceptibility of infection. New antibiotic and adjunct therapies are at an investigational stage but on currently available data are unlikely to make a significant impact on this potentially fatal infection.